2005
DOI: 10.1074/jbc.m509010200
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal RpoN Domain of σ54 Forms an Unpredicted Helix-Turn-Helix Motif Similar to Domains of σ70

Abstract: The "" subunit of prokaryotic RNA polymerase allows genespecific transcription initiation. Two families have been identified, 70 and 54 , which use distinct mechanisms to initiate transcription and share no detectable sequence homology. Although the 70 -type factors have been well characterized structurally by x-ray crystallography, no high resolution structural information is available for the 54 -type factors. Here we present the NMR-derived structure of the C-terminal domain of 54 from Aquifex aeolicus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Structural information on σ N was limited to NMR structures of isolated domains [CBD (18) and RpoN domain (14,17)] and a 3.8-Å resolution crystal structure of Eσ N that revealed the overall disposition of the σ N domains in complex with RNAP but is shown here to contain significant errors in detail (Figs. S3-S5 and SI Appendix, Tables S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural information on σ N was limited to NMR structures of isolated domains [CBD (18) and RpoN domain (14,17)] and a 3.8-Å resolution crystal structure of Eσ N that revealed the overall disposition of the σ N domains in complex with RNAP but is shown here to contain significant errors in detail (Figs. S3-S5 and SI Appendix, Tables S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution NMR structures of the core-binding domain (CBD; Fig. 1B), the RpoN domain, and the RpoN domain in complex with −24 element DNA were determined using Aae σ N domains (14,17,18). The DNA templates for most of our biochemical and structural studies were based on the Aae dhsU promoter (16), which corresponds to the consensus σ N promoter (Fig.…”
Section: Significancementioning
confidence: 99%
“…The C-terminal domain allows specific binding of the activator to a particular UAS (Doucleff et al, 2005b), limiting the activity of the EBP to a few promoters in the chromosome; this fact allows the s 54 factor to be involved in the transcription of different non-related pathways in the same bacterium. Functional EBPs without an HTH motif have been described in Helicobacter pylori, Chlamydia trachomatis and Rhodobacter sphaeroides (Brahmachary et al, 2004;Poggio et al, 2005;Beck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Within these regions a distinctive signature of the EBPs is the GAFTGA sequence that is located in the C3 region; experimental evidence suggests that this sequence interacts with Es 54 during ATP hydrolysis (Chaney et al, 2001; De Carlo et al, 2006). For some activators such as DctD, NifA and PspF, it has been shown that, in the absence of the N-and C-terminal domains, the central region by itself is sufficient to activate transcription (Xu et al, 2004).The C-terminal domain allows specific binding of the activator to a particular UAS (Doucleff et al, 2005b), limiting the activity of the EBP to a few promoters in the chromosome; this fact allows the s 54 factor to be involved in the transcription of different non-related pathways in the same bacterium. Functional EBPs without an HTH motif have been described in Helicobacter pylori, Chlamydia trachomatis and Rhodobacter sphaeroides (Brahmachary et al, 2004;Poggio et al, 2005;Beck et al, 2007).…”
mentioning
confidence: 99%
“…Region III (amino acids 121-477) has functional modules that include determinants that are able to bind core RNAP (amino acids 120-215) and promoter DNA (amino acids 329-463). In particular, the C-terminal module contains a sub-region (amino acids 329-346) that may be cross-linked to DNA and a signature motif for r 54 proteins called an RpoN box (amino acids 454-463) [12,13], which has been shown to contain a classical helix-turn-helix module that is able to bind to the À24 promoter elements [14,15]. In r…”
mentioning
confidence: 99%